Deism, freethinking and toleration in Enlightenment England. Issue 4 (19th May 2017) - Lucci, Diego
ABSTRACT: Focusing on John Toland, Anthony Collins and Matthew Tindal, this article argues that the English deists' tolerationist ideas played a significant role in their religious thinking, which consisted of their 'religious thoughts' and their 'thoughts about religion'. As regards their 'religious thoughts', those deists regarded rationality as the highest state of human existence, because only the proper use of reason could lead humanity to true morality, happiness and (at least in Tindal's case) eternal salvation. Thus, they considered toleration, entailing freedom of conscience, thought and expression, as a necessary means to enable humankind to pursue 'true religion', namely rationality. As to their 'thoughts about religion', they appropriated and rethought the foundational sources and tenets of the Judeo-Christian tradition (and, in Toland's case, of Islam as well) for a twofold purpose: they attempted to debunk the divine right system of power, which opposed toleration and was widely considered to be based on Christian texts and principles; moreover, they aimed at assimilating the original versions of the three major Abrahamic religions, which in their opinion taught morality and toleration, into their own deistic worldviews, which they tried to prove truer and historically more reliable than the positive religions of their time.